PHARMACOGNOSTIC CHARACTERIZATION, PHYTOCHEMICAL SCREENING, AND MICROBIOLOGICAL QUALITY EVALUATION OF BEAN LEAF (Phaseolus vulgaris L.) SIMPLICIA: PHARMACOGNOSTIC CHARACTERIZATION, PHYTOCHEMICAL SCREENING, AND MICROBIOLOGICAL QUALITY EVALUATION OF BEAN LEAF (Phaseolus vulgaris L.) SIMPLICIA - Nurul Istiqomah; Dhevi Indah Puspita Sari; Faizatul Fitria; Muh. Shofi; Siti Munawaroh (JURNAL PHARMA BHAKTA, 2026)
ABSTRACT Background: Common bean leaves (Phaseolus vulgaris L.) are horticultural plant materials with potential use as traditional herbal medicine due to their diverse secondary metabolites that exhibit various health-promoting properties. Pharmacognostic characterization and quality evaluation are essential to ensure the quality and safety of herbal raw materials. Objective: This study aimed to determine the microscopic characteristics, moisture content, loss on drying, phytochemical profile, and microbiological quality of common bean leaves. Methods: This study was conducted using a descriptive approach. Common bean leaf simplicia was extracted by maceration using 70% ethanol. Microscopic observations were performed on fresh leaves and powdered simplicia. Quality evaluation included the determination of moisture content, loss on drying, phytochemical screening, and microbial contamination through Total Plate Count and Yeast and Mold Count analyses. Results: The extraction process yielded an extract recovery of 11.78%. Microscopic analysis revealed the presence of epidermal tissues, stomata, trichomes, and sclerenchyma. The moisture content and loss on drying were 3.0% and 2.1%, respectively. Phytochemical screening indicated the presence of alkaloids, flavonoids, saponins, tannins, triterpenoids, and steroids. The Total Plate Count and Yeast and Mold Count were 1.6 × 10⁵ CFU/g and 3.1 × 10³ CFU/g, respectively. Conclusion: Common bean leaves possess distinctive pharmacognostic characteristics, contain various potentially bioactive secondary metabolites, and meet microbiological quality requirements for use as herbal raw materials. Keywords: Phaseolus vulgaris L., pharmacognostic characteristics, phytochemical screening, microbiological quality